2020
DOI: 10.1186/s12935-020-01417-2
|View full text |Cite
|
Sign up to set email alerts
|

circ_0084927 promotes cervical carcinogenesis by sponging miR-1179 that suppresses CDK2, a cell cycle-related gene

Abstract: Background: Cervical cancer (CC) is a malignant tumor found in the lowermost part of the womb. Evolving studies on CC have reported that circRNA plays a crucial role in CC progression. In this study, we investigated the main function of a novel circRNA, circ_0084927, and its regulatory network in CC development. Methods: qRT-PCR was applied to evaluate the expression of circ_0084927, miR-1179, and CDK2 mRNA in CC tissues and cells. Dual-luciferase reporting experiments and RNA immunoprecipitation (RIP) assay w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Some researchers indicated that miR-1179 promoted cell invasion in esophageal squamous cell carcinoma (Jiang et al, 2015). MiR-1179 has been also identified as a suppressor in several cancers such as human non-small cell lung cancer (Heller et al, 2018), gastric cancer , papillary thyroid carcinoma (Ye et al, 2020) and cervical cancer (Qu et al, 2020). Interestingly, consistently with the effect of miR-1179 in other cancers, our study also supports the inhibitory role of miR-1179 in cervical cancer, as miR-1179 suppressed the cervical cancer cells invasion.…”
Section: Discussionsupporting
confidence: 85%
“…Some researchers indicated that miR-1179 promoted cell invasion in esophageal squamous cell carcinoma (Jiang et al, 2015). MiR-1179 has been also identified as a suppressor in several cancers such as human non-small cell lung cancer (Heller et al, 2018), gastric cancer , papillary thyroid carcinoma (Ye et al, 2020) and cervical cancer (Qu et al, 2020). Interestingly, consistently with the effect of miR-1179 in other cancers, our study also supports the inhibitory role of miR-1179 in cervical cancer, as miR-1179 suppressed the cervical cancer cells invasion.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown that the expression levels of CDK2, CDK4 and CDK6 are often upregulated in various types of cancer, and are associated with tumorigenesis by interacting with other proteins ( 22 , 23 ). For example, Qu et al ( 24 ) reported that CDK2 served a key role in circular RNA (circ)_0084927/microRNA (miR)-1179 signaling axis-mediated cervical cancer development. Zhao et al ( 25 ) found that CDK6 knockdown suppressed gastric cancer cell proliferation via regulating the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the speed and accuracy of the molecular docking approaches have been enhanced and these methods now play a noteworthy role in structure-based drug design. The newly synthesized hybrids were gauged using in silico docking studies for acquiring an additional apprehension of the binding pattern of the target ligands with the cyclin-dependent kinase 2 (CDK2), whose overexpression causes dysfunction of the cell cycle, which is thoroughly allied with hyperproliferation of cancer cells. Numerous evidences have been put forward in the literature sustaining the concept of restraining cancer progression by aiming CDK2. In various categories of human tumors, the dysregulation of CDK2 is noticed, thereby for anticancer therapy, making CDK2 a promising drug target. , In breast cancer progression, CDK2 is considered accountable for activating and phosphorylating the receptor hormones. CDK2 structure with Protein Data Bank (PDB) ID: 2R3I was recruited for carrying out molecular docking studies owing to its higher resolution (1.28 Å) and nonmutated monomeric form.…”
Section: Introductionmentioning
confidence: 99%